Air quality deterioration episode associated with a typhoon over the complex topographic environment in central Taiwan - C.-Y. Lin (Copernicus Publications, 2021)
Air pollution is typically at its lowest in Taiwan during summer. The mean concentrations of PM10, PM2.5, and daytime ozone (08:00–17:00 LST) during summer (June–August) over central Taiwan were 35–40 µg m−3, 18–22 µg m−3, and 30–42 ppb, respectively, between 2004 and 2019. Sampling analysis revealed that the contribution of organic carbon (OC) to PM2.5 could have exceeded 30 % in urban and inland mountain sites during July in 2017 and 2018. Frequent episodes of air quality deterioration occur over the western plains of Taiwan when an easterly typhoon circulation interacts with the complex topographic structure of the island. We explored an episode of air quality deterioration that was associated with a typhoon between 15 and 17 July 2018 using the Weather Research Forecasting with Chemistry (WRF-Chem) model. The results indicated that the continual formation of low-pressure systems or typhoons in the area between Taiwan and Luzon island in the Philippines provided a strong easterly ambient flow, which lasted for an extended period between 15 and 17 July. The interaction between the easterly flow and Taiwan's Central Mountain Range (CMR) resulted in stable weather conditions and weak wind speed in western Taiwan during the study period. Numerical modeling also indicated that a lee side vortex easily formed, and the wind direction could have changed from southwesterly to northwesterly over central Taiwan because of the interaction between the typhoon circulation and the CMR. The northwesterly wind coupled with a sea breeze was conducive to the transport of air pollutants from the coastal upstream industrial and urban areas to the inland area. The dynamic process for the wind direction changed given a reasonable explanation for why the observed SO<msubsup>42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="310c409436de724d2b31553f6031e416"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-16893-2021-ie00001.svg" width="13pt" height="17pt" src="acp-21-16893-2021-ie00001.png"/></svg:svg> became the major contributor to PM2.5 during the episode. SO<msubsup>42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="6051c44ba131ac206db43e824688e92d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-16893-2021-ie00002.svg" width="13pt" height="17pt" src="acp-21-16893-2021-ie00002.png"/></svg:svg> contribution proportions (%) to PM2.5 at the coastal, urban, and mountain sites were 9.4 µg m−3 (30.5 %), 12.1 µg m−3 (29.9 %), and 11.6 µg m−3 (29.7 %), respectively. Moreover, the variation of the boundary layer height had a strong effect on the concentration level of both PM2.5 and ozone. The lee vortex and land–sea breeze, as well as the boundary layer development, were the key mechanisms in air pollutant accumulation and transport. As typhoons frequently occur around Taiwan during summer and fall, their effect on the island's air quality merits further research attention.